Taksonomi Linguistik, Analisis Kesalahan Bahasa dalam Pembelajaran Insya - Parhan, Parhan; Maksum, Ghufron (STAINI Press, 2022)
Mastering Arabic for other speakers is not easy. Because it will be faced with several abilities that make him to be able to master the language. taught and learned by other speakers is not easy. Students may have difficulty learning as their second language. And some of them have errors during the application of this language, and these mistakes both in writing and in speech. This research is related to the analysis of linguistic errors in the construction of fourth semester students of the Tarbiyah Faculty of Arabic Language Education study program at the Nurul Iman Parung Islamic College of Bogor. The method used in this research is quantitative methods in the form of data collection using tests. Then group errors and interpret Corder's opinions. Based on the test results, it was found that the general error in the third semester student construction tasks of the Tarbiyah Faculty of Arabic Language Education study program at the Nurul Iman Parung Islamic High School Bogor was 29 mistakes. Then classify it based on linguistics into four parts: Phonological errors (11 errors), Morphological errors (7 errors), syntax errors (6 errors), Semantic errors and word 5 errors.